The Impact of Elite Split and Coalition Switching on the Hung Parliament Outcome in the 2022 Malaysian General Election - Ramadhan, Muhammad (UI Scholars Hub, 2024)
Malaysia's 2022 General Election resulted in a hung parliament, a new precedent in Malaysia's elections. The Hung parliament means no party or coalition can create a government. Pakatan Harapan and Barisan Nasional, which each got 82 and 30 seats, have to form a coalition to create a unity government. This research analysed how and why the 2022 General Election resulted in a hung parliament. This research uses a qualitative method, which includes the curation of parliamentary seats and election results. Using the Elite Split Theory, this research argues that the hung parliament result in Malaysia's 2022 General Election was caused by elite split that resulted in coalition and party fragmentation. This research found that the elite split in the Dewan Rakyat in 2020-2022 affected the split of the party coalition that controlled the majority of the parliament. This research also found that the effectiveness of the elite split done by the party and individual members of the Dewan Rakyat is different.